2018
DOI: 10.1177/1177271918785130
|View full text |Cite
|
Sign up to set email alerts
|

Nattokinase: A Promising Alternative in Prevention and Treatment of Cardiovascular Diseases

Abstract: Cardiovascular disease (CVD) is the leading cause of death in the world and our approach to the control and management of CVD mortality is limited. Nattokinase (NK), the most active ingredient of natto, possesses a variety of favourable cardiovascular effects and the consumption of Natto has been linked to a reduction in CVD mortality. Recent research has demonstrated that NK has potent fibrinolytic activity, antihypertensive, anti-atherosclerotic, and lipid-lowering, antiplatelet, and neuroprotective effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 56 publications
2
81
0
2
Order By: Relevance
“…They found that a single dose of NK administration could enhance fibrinolysis and anticoagulation via several different pathways simultaneously. (Chen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a single dose of NK administration could enhance fibrinolysis and anticoagulation via several different pathways simultaneously. (Chen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nattokinase was widely studied as a dietary supplement and nutritional food, which has potential to prevent and treat CVDs (Dabbagh et al, ; Weng, Yao, Sparks, & Wang, ). Hongjie Chen et al reported that nattokinase was a promising alternative in prevention and treatment of cardiovascular diseases by possessing a variety of favorable cardiovascular effects, such as fibrinolytic activity, antihypertensive, antiatherosclerotic, and lipid‐lowering, antiplatelet, and neuroprotective effects (Chen et al, ). The consumption of natto has been linked to a reduction in CVD mortality.…”
Section: Introductionmentioning
confidence: 99%
“…15,21 In addition, NK has comparatively strong fibrinolytic/anticoagulant activity, stability in the gastrointestinal tract, and long bioavailability in vivo. 16 NK could possibly offer potential advantages over other currently used pharmaceutical agents for treatment and/or prevention of selected diseases processes. Kim et al has also demonstrated the efficacy of oral Nattokinese administration for the reduction of SBP/DBP in 73 subjects with prehypertension/stage 1 hypertension after 8 weeks of NK intake.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additional research has demonstrated in both human and animal studies that NK has potent fibrinolysis activity, lipidlowering, antihypertensive, antiplatelet/anticoagulant, and neuroprotective effects. 12,[14][15][16] In current study, we have evaluated the efficacy and safety of NK containing supplements (Nattospes) as an adjuvant for the management of the subacute stage and rehabilitation of ischemic stroke. Nattospes were added to the standard of care (SOC) treatment protocol, which included electroacupuncture and Naatrapyl (Piracetam).…”
Section: Introductionmentioning
confidence: 99%
“…Nattokinase is an alkaline enzyme that isolated from the sticky component of natto or a cheese-like food made of soybeans fermented with B. subtilis . Nattokinase cleaves cross-linked fibrin and it possesses fibrinolytic/antithrombotic activity, antihypertensive, antiplatelet, anti-atherosclerotic and neuroprotective actions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%